2009
DOI: 10.1007/s00442-009-1284-2
|View full text |Cite
|
Sign up to set email alerts
|

Intact amino acid uptake by northern hardwood and conifer trees

Abstract: Empirical and modeling studies of the N cycle in temperate forests of eastern North America have focused on the mechanisms regulating the production of inorganic N, and assumed that only inorganic forms of N are available for plant growth. Recent isotope studies in field conditions suggest that amino acid capture is a widespread ecological phenomenon, although northern temperate forests have yet to be studied. We quantified fine root biomass and applied tracer-level quantities of U-(13)C(2)-(15)N-glycine, (15)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 52 publications
3
42
0
Order By: Relevance
“…1). Competition-induced declines in decomposition rate in EEM ecosystems are further supported by natural abundance and 15 N-labelling studies that show that EEM plants acquire more organic N from the soil than do AM plants 13,21 , and that experimental exclusion of EEM fungi increases the rate of organic matter decomposition 7 by increasing the biomass of free-living microbes and the activity of their C-degrading enzymes 6 . In contrast, the exclusion of AM fungi from the soil reduces the rate of decomposition by reducing the substrate supply to free-living decomposers 22 .…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…1). Competition-induced declines in decomposition rate in EEM ecosystems are further supported by natural abundance and 15 N-labelling studies that show that EEM plants acquire more organic N from the soil than do AM plants 13,21 , and that experimental exclusion of EEM fungi increases the rate of organic matter decomposition 7 by increasing the biomass of free-living microbes and the activity of their C-degrading enzymes 6 . In contrast, the exclusion of AM fungi from the soil reduces the rate of decomposition by reducing the substrate supply to free-living decomposers 22 .…”
mentioning
confidence: 84%
“…In contrast, the exclusion of AM fungi from the soil reduces the rate of decomposition by reducing the substrate supply to free-living decomposers 22 . Greater soil C storage in EEM ecosystems than in AM ecosystems at the large spatial scale reported here demonstrates that fine-scale mechanistic studies on the functionality of mycorrhizal symbioses-including N uptake preferences 13,21 , partitioning of plant-C belowground 23 , productivity 24 and decomposition 7,22 -can be scaled up to predict the consequences of AM versus EEM symbioses at the ecosystem-to-global scale.…”
mentioning
confidence: 86%
“…Also, a few studies have shown that temperate trees have the ability to use amino acid N (Bennett and Prescott 2004;Hofmockel et al 2007;Warren and Adams 2007). In an attempt to link plant nutrition with patterns of amino acid versus inorganic N availability, Finzi and Berthrong (2005); Gallet-Budynek et al (2009) compared root uptake of 15 N-labeled amino acids among several forest ecosystems and found, in general, that roots from sites with slower rates of N mineralization had a higher 15 N content than those from more fertile sites. Neither study identified the roots to species, though, so it is unclear how different species of plants varied in their use of amino acid versus inorganic forms of N. However, oak-beech-hemlock forests dominated the low-fertility sites of both studies, while sugar maple-white ash forest dominated the high-fertility sites, suggesting that the shift in uptake rates of glycine by roots was at least partly driven by species replacement.…”
Section: Introductionmentioning
confidence: 98%
“…However, there is growing evidence that amino acid pools are relatively more abundant in temperate forests where N mineralization rates are low (Finzi and Berthrong 2005;Gallet-Budynek et al 2009;Rothstein 2009), providing a pool of potentially plant-available N in what were previously considered low-fertility habitats. Also, a few studies have shown that temperate trees have the ability to use amino acid N (Bennett and Prescott 2004;Hofmockel et al 2007;Warren and Adams 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Eastern hemlocks form ecto-mycorrhizal fungal (EMF) associations and produce roots that strongly increase soil enzyme activities, suggesting a greater importance of organic N cycling relative to the ash forests (Gallet-Budynek et al 2009, Brzostek and.…”
Section: Sitementioning
confidence: 99%